Different Bla‐g T cell antigens dominate responses in asthma versus rhinitis subjects. Issue 12 (December 2015) - Dillon, M. B. C.; Schulten, V.; Oseroff, C.; Paul, S.; Dullanty, L. M.; Frazier, A.; Belles, X.; Piulachs, M.‐D.; Visness, C.; Bacharier, L.; Bloomberg, G. R.; Busse, P.; et al.
Summary: Background and objective: The allergenicity of several German cockroach (Bla‐g) antigens at the level of IgE responses is well established. However, less is known about the specificity of CD4 + TH responses, and whether differences exist in associated magnitude or cytokine profiles as a function of disease severity. Methods: Proteomic and transcriptomic techniques were used to identify novel antigens recognized by allergen‐specific T cells. To characterize different TH functionalities of allergen‐specific T cells, ELISPOT assays with sets of overlapping peptides covering the sequences of known allergens and novel antigens were employed to measure release of IL‐5, IFNγ, IL‐10, IL‐17 and IL‐21. Results: Using these techniques, we characterized TH responses in a cohort of adult Bla‐g‐sensitized subjects, either with ( n = 55) or without ( n = 17) asthma, and nonsensitized controls ( n = 20). T cell responses were detected for ten known Bla‐g allergens and an additional ten novel Bla‐g antigens, representing in total a 5‐fold increase in the number of antigens demonstrated to be targeted by allergen‐specific T cells. Responses of sensitized individuals regardless of asthma status were predominantly TH 2, but higher in patients with diagnosed asthma. In asthmatic subjects, Bla‐g 5, 9 and 11 were immunodominant, while, in contrast, nonasthmatic‐sensitized subjects responded mostly to Bla‐g 5 and 4 and the novel antigen NBGA5. Conclusions: Asthmatic and nonasthmatic cockroach‐sensitized individuals exhibit similar TH 2‐polarized responses. Compared with nonasthmatics, however, asthmatic individuals have responses of higher magnitude and different allergen specificity.